2005
DOI: 10.1002/jcb.20474
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator‐activated receptor‐γ by troglitazone (TGZ) inhibits human lung cell growth

Abstract: Peroxisome proliferator-activated receptor-gamma (PPAR-gamma) is a member of the nuclear hormone receptor superfamily of ligand-activated transcription factors and a crucial regulator of cellular differentiation. PPAR-gamma ligands have been demonstrated to inhibit growth of several cancer cells. In this study, two human lung cancer cells (NCI-H23 and CRL-2066) and one human lung normal cell (CRL-202) were used for the experiments. The results showed that in consistence with the loss of viability, troglitazone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 50 publications
7
56
1
Order By: Relevance
“…The human nonsmall cell lung cancer (NSCLC) cells, NCI-H23, were grown in 100-mm tissue culture disks as previously described [19].…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The human nonsmall cell lung cancer (NSCLC) cells, NCI-H23, were grown in 100-mm tissue culture disks as previously described [19].…”
Section: Cell Culturementioning
confidence: 99%
“…Cell proliferation was measured with dimethylthiazolyldiphenyltetrazolium-bromide (MTT) as previously described [19]. Cell proliferation was further confirmed by bromodeoxyuridine labelling of DNA, performed according to the manufacturer's instructions (Roche Applied Science, Penzberg, Germany).…”
Section: Assessment Of Cell Proliferation and Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found that PPARÁ is overexpressed in various types of tumor cells and PPARÁ agonists can induce apoptosis (44,45). It has been reported that ChR derivatives induce apoptosis of human hepatocellular carcinoma and human gastric cancer cells by activating PPARÁ (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Further, ciglitazone is reported to induce differentiation and apoptosis in non small cell lung cancer [16]. In addition, the TZDs have been found to decrease lung cancer induced angiogenesis and to limit proliferation [17]. We recently have found that different TZDs have the capacity to modulate arachidonic acid metabolism by a variety of pathways [18].…”
Section: Introductionmentioning
confidence: 99%